The significance of capillary electrophoresis in the detection of haemoglobin constant spring and its relationship with high-performance liquid chromatography - Rameli, Nabilah (2021)
Introduction: Haemoglobin Constant Spring (Hb CS) is one of the most common non-deletional types of alpha (α) thalassaemia in Southeast Asia region. The nature of this abnormal globin gene is that it is unstable, labile and is present in minute amount in the peripheral blood. Thus, this may lead to underdiagnosis of the disease. This study was conducted to determine the proportion of Hb CS among the Kelantan population and to compare range of peak value in Zone 2 CE findings for 3 groups of Hb CS (heterozygous, homozygous, and compound heterozygous) and their haematological parameters. The study aimed to look at the findings of HPLC in relation to CE results in detecting Hb CS. Study design and methods: This was a cross-sectional study involving secondary data collection from 378 samples which showed peak value on Zone 2 of CE. The samples were taken from the National Thalassemia screening of Form 4 students from all districts in Kelantan. The haematological parameters of red cells were analysed using Sysmex XN 3000 automated blood cell analyser, Hb analysis was performed using automated CE system (CAPILLARYS2 Flex-Piercing System Sebia), HPLC Biorad variant II, DNA analysed using multiplex polymerase chain reaction (PCR) and multiplex Amplification refractory mutation system (ARMS) to detect both deletional and non-deletional α-thalassaemia. Results: 376 samples (99.5%) with presence of peak value on Zone 2 of CE were confirmed to have termination codon CS mutation. Heterozygous Hb CS is the most common type of Hb CS detected in 344 samples (91.5%), followed by compound heterozygous Hb CS which was 31 samples (8.2%) and only 1 sample (0.3%) of homozygous Hb CS. The mean ± SD of peak value in Zone 2 of heterozygous Hb CS and compound heterozygous Hb CS were 0.61 ± 0.13 and 0.77 ± 0.34 respectively. The only sample of homozygous Hb CS showed the value of 4.9% of peak value in Zone 2 of CE. The significant differences of haematological parameters between heterozygous and compound heterozygous Hb CS were observed in haemoglobin level, MCV, MCH and MCHC. This study showed there was a good linear correlation between peak in C-window on HPLC and peak value in Zone 2 of CE in detecting Hb CS, r=0.73. Conclusion: Thus, by combining the haematological parameters and complementary tests of both CE and HPLC, the diagnosis of Hb CS can be detected prior to confirmation by DNA molecular study that is far more expensive.